The Role Of Cognitive Dissonance In Shaping Relationship Dynamics Among Teenagers And Adults - Gill, Muskaan; Meenakshi, Meenakshi (Journal of Neonatal Surgery, 2025)
Cognitive dissonance is an important aspect of influencing interactions between people, especially in the case of intimate relationships. It occurs when two or more conflicting beliefs, values, or behaviors cause psychological distress, prompting people to resolve the issue through various coping strategies. The study looks at how this psychological tension affects interpersonal relationships across various age groups, with an emphasis on emotional well-being and decision-making. Through the investigation of intrinsic as well as external causes of cognitive inconsistency, the study seeks to investigate its impacts on sustaining or destroying social connections. A mixed-methods technique was used whereby structured questionnaires and statistical package tools were employed to measure reaction from a multi-faceted sample. Results show that while cognitive dissonance does have an effect on relationship dynamics, it is generally weak, with other psychological and social factors being more influential towards relationship stability. The study underlines the necessity of promoting emotional regulation, self-awareness, and open communication to mitigate ill effects. Synthesizing cross-cultural studies and neurological study can further enrich the understanding of how individuals resolve competing emotions and beliefs. Investigation of these areas can enhance methods of enhancing social interaction and emotional resilience in professional and personal environments.